"Selected Papers from the 2nd Ellisras Longitudinal Study and Other Non-Communicable Diseases Studies International Conference" Special Issue Editorial - Kotsedi Daniel Monyeki (MDPI AG, 2021)
Epidemics of non-communicable diseases (NCDs) are presently emerging and on the increase in South Africa. It is increasingly recognized that the occurrence of adult chronic disease are influenced by factors operating from childhood, which are sustained throughout the individual's life course. Increased risk may start in infancy or even before birth and will continue to be influenced by health related behavior during adulthood. The academic level of people in the community influence the level of their health status. Commitment to the promotion of health through prevention, education, and suitable management is the building block for creating a healthy society. The community must make strides to shift from traditional knowledge and medication, and seek new innovative ways of addressing issues facing the population with regard to obesity, overweight, hypertension health, smoking cessation, alcohol abuse, and low physical activity in line with a healthy living lifestyle. The NCDs pose health problems in South Africa and deserve more attention. Poor control of obesity, hypertension, and diabetes, to name just a few, only adds to the current problems. The South African government and the business sector of South Africa should provide safe walking/riding trails in the cities and in rural area to combat emerging NCDs that are killing our community members indiscriminately without considering race, gender, age, and place of residence. Compulsory introduction of physical education lessons to all public schools cannot be over emphasized in the current escalating NCD situation in South Africa.